2000
DOI: 10.1054/bjoc.2000.1356
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of S100A6 at the invading fronts of the primary lesion and liver metastasis in patients with colorectal adenocarcinoma

Abstract: Two members of the S100 gene family, S100A6 and S100A4 have been suggested to be associated with cancer invasion and metastasis. To study their involvement in the malignancy of human colorectal adenocarcinoma, we examined the protein expression levels of S100A6 and S100A4 in the primary colorectal adenocarcinoma (T) and paired adjacent normal colorectal mucosa (N) from 12 cases, quantitatively by Western blot analysis. In 11 of 12 and seven of 12 cases, S100A6 and S100A4 expression levels were higher in T than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
55
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 15 publications
7
55
1
1
Order By: Relevance
“…However, the result was found not to be statistically significant (Komatsu et al, 2001). Whilst it is possible that S100A4 protein was also elevated in the adjacent normal tissue, it is more likely that this result arises from variability in the levels of S100A4 in the carcinoma specimens as measured by Western blotting, due to the presence of S1004 in infiltrating lymphocytes, as found in the present study.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, the result was found not to be statistically significant (Komatsu et al, 2001). Whilst it is possible that S100A4 protein was also elevated in the adjacent normal tissue, it is more likely that this result arises from variability in the levels of S100A4 in the carcinoma specimens as measured by Western blotting, due to the presence of S1004 in infiltrating lymphocytes, as found in the present study.…”
Section: Discussioncontrasting
confidence: 71%
“…When the S100A4 levels in epithelial cells were compared immunocytochemically (Table 2), the proportion of specimens exhibiting epithelial staining for S100A4 was more strongly significantly different between carcinomas and normal colon (P=0.0016, Fisher exact test) than when specimens were compared using the quantitative RT -PCR technique (P=0.05, Fisher exact test). The quantitative RT -PCR technique, like the Western blotting used by Komatsu et al (2001) does not distinguish between staining of epithelial and infiltrating host cells.…”
Section: Discussionmentioning
confidence: 99%
“…The only other published study, which to our knowledge examined the effect of S100A6 on motility, showed a decrease in the motility of one of three osteosarcoma cell lines after adenoviral-mediated overexpression of S100A6 (Luu et al, 2005). Interestingly in osteosarcoma, a trend was observed between decreased metastasis and increased S100A6 staining, contrasting the findings in melanoma and colorectal cancer (Maelandsmo et al, 1997;Komatsu et al, 2000). Whether S100A6 contributes to pancreatic cancer cell motility through interaction with annexin 2 is not yet clear.…”
Section: Discussionmentioning
confidence: 73%
“…Although S100A6 overexpression in pancreatic and other cancers, including gastric (Yang et al, 2007), thyroid (Brown et al, 2006), breast (Cross et al, 2005) and colorectal (Komatsu et al, 2000) has been documented, its precise role in cancer is not known. In pancreatic cancer, the expression of S100A6 appears to correlate with aggressive disease in that high levels of tumour S100A6 are associated with poorer outcome (Vimalachandran et al, 2005), whereas pancreatic cancer cells depleted of S100A6 are less invasive (Ohuchida et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation